Study to identify strategies and programmes to eradicate poverty and improve employment and equity restructuring in the state of sabah: component 3 – qualitative - Rosazman Hussin; Dayang Suria Mulia; Jalihah Md Shah; Asmady Idris (Universiti Malaysia Sabah, 2009)
No abstract